Return of Visual Acuity to Normal in Old Age - Misra, A (Kathmandu University Medical Journal, 2015)
Changes occur in our body through out life. Decreased visual acuity is probably the most common effect of age-related anatomical and neurological changes in the eyes and the visual pathway. However, this case is an exception as at the age of 75 years, his power of accommodation has returned to normal. The improvement in accommodation and visual acuity is hard to explain. Likely explanations given need to be further investigated. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12495 Kathmandu University Medical Journal Vol.11(2) 2013: 165-167